1979
DOI: 10.1346/ccmn.1979.0270603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Strength and Ion Pair Formation on the Adsorption of Nickel by Kaolinite

Abstract: Abstract---Adsorption of Ni(II) by Ca-and Na-saturated kaolinites was studied in equilibrating solutions with total Ni concentrations ranging from 118 to 946/xg/liter. Background electrolytes used in these :experiments were 0.005, 0,0l, 0.025, and 0.5 M Ca(NO3)~, 0.002 and 0.005 M CaSO4,0.0l and 0.1 M NaNO3, and 0.005 and 0.05 M Na2SO4. Ion speciation in equilibrium solutions was calculated by the computer program GEOCHEM. Computed Ni 2+ concentrations and activities at equilibrium were correlated with total N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 20 publications
1
23
0
2
Order By: Relevance
“…Albee (1962) reported that in natural chlorites, small amounts of Cr do substitute Si. Mattigod et al (1979) studied the adsorption of Ni onto kaolinite and found that increasing ionic strength decreases adsorption of Ni. Thus, the low salinity in the upper middle estuary must be facilitating the adsorption of Ni onto kaolinite as compared to the other locations in the estuary.…”
Section: Geochemistry Of Sedimentsmentioning
confidence: 99%
“…Albee (1962) reported that in natural chlorites, small amounts of Cr do substitute Si. Mattigod et al (1979) studied the adsorption of Ni onto kaolinite and found that increasing ionic strength decreases adsorption of Ni. Thus, the low salinity in the upper middle estuary must be facilitating the adsorption of Ni onto kaolinite as compared to the other locations in the estuary.…”
Section: Geochemistry Of Sedimentsmentioning
confidence: 99%
“…The Ni 2+ cation is known to form complexes with various organic and inorganic ligands (Bowman et al, 1981). Many studies have considered the effect of cations and anions that constitute the electrolyte support on metal adsorption, principally regarding to the competitive effect of Ca 2+ for adsorption sites and by the action of Cl -in the formation of chloride complexes with less affinity for the surface (Mattigod et al, 1979;Bowman et al, 1981;Wang et al, 1997;Echeverría et al, 2003). Considering the nature of electrolyte support, the effect of the competition between Ca 2+ and Ni 2+ for the same adsorption sites probably justified the decrease in Ni adsorption with the increase in ionic strength, rather than the probable formation of complexes between Ni and the anion because NO 3 -has much less affinity than Cl -for this type of reaction in solution (Criscenty and Sverjensky, 1999).…”
Section: Influence Of Soil Solution Ionic Strength (I) On Ni Adsorptionmentioning
confidence: 99%
“…This aspect is of particular interest for Ni adsorption, because there is no consensus yet on its retention mechanism by the soil. Nickel adsorption has been studied in pure systems, such as Fe, Al and Mn hydrated oxides (McKenzie, 1980;Beukes et al, 2000), clay minerals (Mattigod et al, 1979;Echeverría et al, 2003;Sen Gupta and Bhattacharyya, 2006) and organic matter (Mellis et al, 2004), and in complex systems such as the soil, under natural and agricultural conditions or with residue application (Camargo et al, 1989;Pombo et al, 1989;Mellis et al, 2004;Iglesias et al, 2007). However, sufficient data have not yet been gathered on Ni adsorption by weathered soils of the wet tropics to assure the implementation of efficient prevention techniques and remediation of soil contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Freundlich Langmuir Thermodynamic parameters [25,26]. These two solution effects cause decreasing adsorption of Cr(VI) to S. aureus biomass surfaces with a net positive charge.…”
Section: Temperature (K)mentioning
confidence: 99%